Tramadol and hypoglycaemia: comparison with other step 2 analgesic drugs. (15th March 2013) - Bourne, Cindy; Gouraud, Aurore; Daveluy, Amélie; Grandvuillemin, Aurélie; Auriche, Pascal; Descotes, Jacques; Vial, Thierry; ,
Abstract : Aims: The risk of hypoglycaemia with tramadol (TRM) is not well described. Our aim was to analyze spontaneous reports of hypoglycaemia registered in the French Pharmacovigilance database and to compare these data with two other step‐2 analgesic drugs. Methods: Cases of hypoglycaemia associated with TRM, dextropropoxyphene (DXP) and codeine (COD) recorded between 1997 and November 2010 in the French pharmacovigilance database were compared. Results: Seventy‐two cases of hypoglycaemia associated with DXP and 43 with TRM were retained for evaluation (the single case reported with COD was not further considered). Most patients were elderly people with no significant difference in age between DXP‐ and TRM‐treated patients (71.2 ± 21 vs . 69.4 ± 22.5 years). Hypoglycaemia occurred after a median of 4 and 5 days with DXP and TRM treatment, respectively. The mean lowest serum glucose concentration was 2.1 ± 0.9 mmol l −1 in the DXP group compared with 2.5 ± 1 mmol l −1 in the TRM group ( P = 0.072). At least, one risk factor of hypoglycaemia was found in most patients, with no significant difference between groups (58.3% in the DXP group and 58.1% in the TRM group). In particular, 31.9% patients from the DXP group had diabetes compared with 41.8 % from the TRM group ( P = 0.28) and 18% of DXP patients had renal insufficiency compared with 16.3% of TRM patients ( P = 0.8). Conclusions: Our study confirms that TRM is associated with the occurrence of hypoglycaemia in elderly or predisposed patients, with characteristics similar to those previously reported with DXP.